Full life course analysis of birdsong reveals maturation and senescence of highly repeatable song characteristics. (17th September 2019) - Zipple, Matthew N; Nowicki, Stephen; Searcy, William A; Peters, Susan
Abstract: Signalers may benefit in some contexts from advertising their ages, for example in courting potential mates. Receivers in turn may benefit from assessing a signaler's age, even in cases where their doing so is against the signaler's interests. Indicators of age contained in signals thus may have important fitness consequences for both signalers and receivers. In birds, males of many species have been shown to display delayed maturation of their songs, resulting in older males singing songs that are higher in quality in one or more characteristics. Conversely, it seems possible that songs might eventually deteriorate with age as an aspect behavioral senescence. Studies of birdsong long enough to test both possibilities are quite uncommon, with nearly all studies aspect of age-dependent changes in birdsong spanning 3 or fewer years of males' lives. Here, we present the longest longitudinal analysis of male birdsong to date, in which we analyze songs recorded for 4–11 years of the lives of captive male swamp sparrows. We find that males displayed delayed maturation of three song characteristics: song rate, song length, and consistency between songs. Delayed maturation was followed by behavioral senescence of three characteristics: song rate, stereotypy within songs, and consistency between songs. Because song quality declined in males beyond 2 years of age, this evidence is inconsistent with a signaling system in which females both prefer increasingly older males and are able to accurately determine male age through song assessment. Rather, our evidence suggests that swamp sparrows should be able to use song to distinguish intermediate-aged males from 1-year-old and very old males. Abstract : We show that characteristics of birdsong continue to mature during across early adulthood and then senesce as birds continue to age. Short-term studies (encompassing up to 4 years of birds' lives) have shown that birdsong continues to mature in adult males, and in some cases declines in quality following maturation. Here, we present the longest longitudinal study of age-related changes in a species' birdsong to date, including based on up to 11 years of recordings per individual of songs from hand-reared male swamp sparrows.